Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 623738395 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "Year 1979-2013", "HasGeospatialIssue is false" ] } The dataset includes 623738395 records from 17800 constituent datasets: 281 records from Museu de Ciències Naturals de Barcelona: BGJBB. 2 records from Three new species of the barracudina genus Lestidium (Aulopiformes: Paralepididae) from the Indo-West Pacific. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 216 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 6 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 5356 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 1 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 47 records from Range table from planktonic foraminifers in ODP Hole 180-1110B. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 18181 records from OPIE_National_2017_12_18. 1340 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 753 records from UWIZM Molluscs. 14331 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Trawl. 32 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 90236 records from CAS Herpetology (HERP). 2 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 65 records from Oxic sediment - Extracellular Metagenome. 2418 records from MCP-Aves - Coleção de Aves. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 240 records from (Table 2g) Nannofossil distribution chart of petroleum well Swan-3. 1 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 3079 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 120 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 27132 records from EDP Foz Tua: Terrestrial Birds, Spring (point counts) - Ecological Monitoring Program [2011-2017]. 634 records from Bird specimens of Saitama Museum of Natural History. 87 records from orthopteracollections-nhmj-ioj. 20 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 178 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 887 records from Vertebrados terrestres de San Juan de Camarones, Durango. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 1 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 788 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1034 records from Collections of Bioclass, school #179, Moscow. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 2 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 51 records from Données du/de la naturaliste Houpert Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 189328759 records from EOD - eBird Observation Dataset. 341 records from Mycology collection, Norwegian Forest and Landscape Institute. 256 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 4 records from New seriated Amathia species in Japan, with a redescription of A. acervata Lamouroux, 1824 (Bryozoa: Ctenostomata). 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 83 records from Middlebury College Bee Collection. 5 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 34 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 6881 records from Colección de Solanales del Museo Botánico CORD - IMBIV. 10 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 8 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 6822 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 1 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 171 records from Total foraminifera counts of multinet M21/6_MSN787. 269 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 12853 records from (Table 1) Range table of planktonic foraminifers from ODP Hole 166-1006A sediments. 27 records from UWIZM Anoles. 130 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 2547 records from Pat Livermore's Fungus Records 1976 - 2000. 2 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 1 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 2 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 1185 records from Phytoplankton abundance in surface water during cruise Alkor 237-1. 11 records from Ektomykorrhizen auf VIP Alb (Wald). 335 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part II. 15 records from Benthic macrofauna abundance of sediment core 12930-063. 4987 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 466 records from Pollen analysis of sediment profile TR0 from Truennensee. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 148 records from Überall ist Wunderland. 14101 records from INNS Data: All Taxa (West Wales). 2451 records from Macrobenthos Chukchi Sea, 1986. 5714 records from The Taiwan Roadkill Observation Network Data Set.. 1561 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 184 records from Condamine Alliance. 1 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 4 records from Données naturalistes de Ingénieurs écologues GEREA. 6 records from Distribution And New Records Of Lymexylidae (Coleoptera: Lymexyloidea) In Guatemala And Mexico. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 8046 records from sediment metagenome Metagenome. 16 records from Microzooplankton abundance and biomass at station TT043_13-1. 187 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 7 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 849 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 15 records from Tardigrad collection of the National Museum of Nature and Science. 506 records from (Appendix B) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-966B. 115 records from Données naturalistes de Marie-France LECCIA. 1701 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 1714 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 206 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 121 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 2059 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 18 records from Naturtag. 45 records from données espèces - Expertise IPE 63. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 157 records from Chronicle of Nature - Phenology of Mushrooms of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 25 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 7924 records from Herbier Louis-Marie (QFA) - Collection de lichens. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 5 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 27 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 3 records from Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae) including new species and biological information. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 349 records from USGS Alaska Science Center Polar Bear Maternal Dens. 1709 records from suspended particulate matter Raw sequence reads. 2 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 12576 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 1 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 1878 records from Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 5244 records from (Table 9) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-587. 1997 records from Aves de la cuenca media del río Bogotá. 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 4282650 records from Observations du Conservatoire botanique national du Bassin parisien.. 127 records from Total foraminifera counts of multinet M21/2_MSN650. 177 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 24 records from Steinbruch Mainz-Weisenau, 4.Jahr. 4 records from Colecção Entomológica IIA. 15998 records from MZFC/Coleccion de Aves. 352 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 1292 records from (Table 4) Benthic foraminifera in middle to late Miocene sediments of DSDP Hole 90-588. 951743 records from Tasmanian Natural Values Atlas. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 63 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 623 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 113272 records from Macaulay Library Audio and Video Collection. 1827 records from Museu Darder de Banyoles. 1 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 521 records from Benthic foraminifera abundance of Hole 82-558. 4 records from More new Diplotrema earthworm species from southern Mexico (Annelida, Crassiclitellata, Acanthodrilidae, Acanthodrilinae). 316 records from Moss species from Heard Island, 1987 and 2000. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 36 records from DMNS Egg Collection (Arctos). 274 records from Odonata del Museo de Entomología de la Universidad del Valle. 1421 records from Geochemistry and sedimentology on core POS200/10_6-2. 256 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 2538 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 9723 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 276196 records from Vascular Plants, Field notes, Oslo (O). 3 records from Microplankton counts and carbon biomass at station TT007_10-CTD123. 6 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 167 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 3 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 3371 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 42 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 238 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 1 records from First description of the female of Clubiona milingae Barrion-Dupo, Barrion & Heong, 2013 (Araneae, Clubionidae). 4 records from Cyphocharax boiadeiro, a new species from the upper rio Araguaia, Amazon basin, Brazil (Characiformes: Curimatidae). 4 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 219 records from An updated checklist of aquatic plants of Myanmar and Thailand. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 2 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 1263 records from BioGIS - Bryophytes - HUJ collections. 741 records from (Appendix B) Dinoflagellate cysts in ODP Site 170-1039 sediments. 3362 records from (Table 7) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-873B. 713 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 26653 records from Herbarium Universitatis Daugavpiliensis. 4 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 871 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 1262 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 158 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 64 records from Pilzlehrwald. 2900482 records from International Barcode of Life project (iBOL). 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 601 records from LBV 100 - Artenvielfalt am Rothsee. 48 records from Swedish Malaise Trap Project (SMTP) - small parasitic aculeate families. 385 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 126 records from Abundance of radiolaria at station UT99-5-1. 39 records from Données naturalistes de Xavier BONNET. 18905 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 329791 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1881 records from Plecoptera. 44 records from Flora und Fauna in unserer Kita. 3 records from MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata - E. przewalskii species complex (Squamata, Lacertidae). 43 records from Abundance of coccosphere-units of sediment core GIK23424-3. 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 23657 records from Swan Coastal Plain Survey. 114 records from Flora. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 98 records from Foraminifera species abundances from tow TT011_5-MOC63. 84 records from BIRDRACE Avinauten. 116 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 1 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 10 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 14 records from NZCS Brownsberg Nature Park Monitoring. 154 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 3280 records from La flora útil de dos comunidades indígenas del Valle de Tehuacán-Cuicatlán: Coxcatlán y Zapotitlán de las Salinas, Puebla. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 244 records from Flore des Pyrénées. 73738 records from Lichen field notes, Oslo (O). 1924 records from Collection Mollusca SMF. 45036 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 988 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 9524 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 3 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 16 records from Analyses of the recent components of sediment core PS1277-1. 3167 records from MEXU/Leguminosae. 5870 records from DBRC Arvicola amphibius records 1925 - 2016. 4 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 15 records from Inventaire des mammifères du Parc de la Haute-Île (93). 1072 records from Spider Mites Collection of Jean Gutierrez. 2 records from Ichneumonid wasps from Madagascar. VI. The genus Pristomerus (Hymenoptera: Ichneumonidae: Cremastinae). 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 21 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 26 records from Schulteich Heinrich-Mann-Schule. 16 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 3 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 608 records from (Table 6) Pleistocene nannofossil range chart for ODP Hole 134-830A. 608 records from Range table from benthic foraminifers in ODP Hole 146-889A. 1949 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 717 records from Inventario florístico de las Cactáceas del estado de Tamaulipas, México. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 371 records from Bannwald Burghauser Forst. 130 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 76203 records from R. L. McGregor Herbarium Vascular Plants Collection. 19 records from Coccolith counts of multinet M32/5_MSN988. 1191 records from Phytoplankton abundance in surface water during Professor Vodyanitskiy cruise PV30_1. 12285 records from SEWBReC Bees, Wasps and Ants (South East Wales). 1 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 4 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 5 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 6 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 4 records from A new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Araguaia, Central Brazil. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 3 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 5 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2057 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 12 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 389 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 1 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 154 records from Sorensen distance for herbivores. 219 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 118 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 112 records from Total foraminifera counts of multinet M33/1_MSN1029. 8 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 473 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 12695 records from University of Guam Insect Collection. 36 records from Invasive species - Ruddy duck (Oxyura jamaicensis) in Flanders, Belgium. 127 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 2801 records from National Botanic Garden Belgium - Myxomycetes. 26 records from Dinoflagellate abundance of Hole 81-554. 5 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 2224 records from Amphibian and reptile data for Dumfries and Galloway.. 2661 records from Chronicle of Nature - Phenology of Birds of Pinezhsky State Nature Reserve. 605 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 173 records from Total foraminifera counts of multinet M6/7_MSN100. 20 records from A description of the flea species Paractenopsyllus madagascarensis n. sp. and the female sex of Paractenopsyllus raxworthyi Duchemin & Ratovonjato, 2004 (Siphonaptera, Leptopsyllidae) from Madagascar with a key to the species of Paractenopsyllus. 1 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 4985 records from Données naturalistes de Benoit MARTHA. 54 records from Total foraminifera counts of multinet M21/4_MSN707. 6 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 22558 records from Observations occasionnelles Parc national des Pyrénées. 478 records from Neogene palynomorpha from site 81-552. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 120 records from BIRDRACE The early birds. 1 records from Macaronesian Muscidae (Diptera). I. The genus Hebecnema Schnabl with description of a new Canarian endemic species and a review of the European fauna. 1138 records from RECORD Orthoptera Data. 6 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 51 records from Records of the Victorian Conservation Seedbank. 55 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 1 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 193 records from Relative abundances of Florisphaera profunda and Helicosphaera carteri during the sapropel S5 of sediment core MD81-LC21. 133 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/041-5. 11777 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3003 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 10 records from Oberservation of birds at station PS14/143 along 49° West. 31200 records from The digitization of plant specimens of NTU. 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 851 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 2560 records from Upper Silesian Museum, Bird Observations. 136 records from DREAL Auvergne - Amphibiens - 2015. 554 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 706 records from Données naturalistes de Quentin ROME. 847 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 131 records from Artenvielfalt auf dem Schulgelände. 968 records from Distribution of benthic foraminifera on sediment core sediment core PS1290-4. 110 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 2 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 101 records from Abundance of radiolaria at station UT99-19-2. 417 records from Données Opération escargots. 398 records from Royal BC Museum - Herpetology Collection. 17171 records from North Sea plastic incubation and reference communities, raw sequence reads. 64 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1391. 7765 records from National Museum of Natural Science. 247 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 85 records from Total foraminifera counts from M35/1_MSN1043. 227 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from Global Ocean Sampling Expedition. 71 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 69 records from BIRDRACE Pfeifenten. 7 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 29 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 91 records from Données de la structure ONEMA/AFB provenant de la base de donnée du SINP Île-de-France CETTIA. 69 records from Données de la naturaliste Laurence Beauchamp. 68 records from Range table from benthic foraminifers in ODP Hole 144-874A. 518 records from New Brunswick Museum Collection. 1502 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 13 records from Collections ichtyologiques et herpétologiques (BOUM). 30 records from Range table from planktonic foraminifers in ODP Hole 175-1078C. 7999 records from Données naturalistes de Bruno OGER. 8568 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 3154 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 152 records from Abundance of radiolaria at station LV28-40-2. 1 records from The giant “ penis ” of a newly described species in the subgenus Scotoconiopteryx from Peru (Neuroptera: Coniopterygidae: Coniopteryginae: Coniopteryx). 4 records from Taxonomic revision of Brazilian genus Tyrannoseira Bellini & Zeppelini, 2011 (Collembola, Entomobryidae, Seirinae). 2 records from Données naturalistes de ROLLAND Blandine. 14 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 1 records from A mountain of millipedes VI. New records, new species, a new genus and a general discussion of Odontopygidae from the Udzungwa Mts, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 5372 records from Lichens of North-Eastern Poland. 54 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 330 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 3 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6163 records from NE Scotland fish records 1800-2010. 4 records from Anmerkungen zur Gattung Dapsa L, 1829 (Coleoptera, Endomychidae). 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 3 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 1 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 671 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 18 records from (Table 1) Mean body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 6 records from Coccoliths in sediment core PS1532-9. 61 records from Pycnogonida collection from the Museu Nacional de História Natural e da Ciência da Universidade de Lisboa, Portugal. 3935 records from Lakes ediments of the Amazon River system Raw sequence reads. 97 records from Foraminifera species abundances from tow TT011_7-MOC66. 57913 records from Fichier communal des ongulés. 6 records from Sächsische Schweiz (Pfaffenstein). 564 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_15-CTD162. 29 records from Morphological and anatomical investigation of New Caledonian graminoid Dendrobium (Orchidaceae) with the description of two new species. 4298 records from ColRest_Raw1. 30 records from Chronicle of Nature - Phenology of Arachnids of FSBI Zeya State Nature Reserve. 1026 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 4610 records from Wetland Algae. 5 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 5159 records from SNH Bat Casework records 1970-2007. 216 records from Phytoplankton abundance at station CD46_1305C#2. 4 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 131 records from Abundance of dead benthic foraminifera in sediment core CD86_05_BC5. 2354 records from Recopilación de Información de FLORA en la Jurisdicción de CORNARE, hasta el año 2015. 2145 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 1357 records from Chronicle of Nature - Phenology of Plants of Kaniv Nature Reserve. 25 records from Living Cirripedia. 3 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 501 records from Planktic foraminifera abundance of Hole 74-525B. 1284 records from Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 900 records from Naturhistorisches Museum Mainz, Botanical Collection. 604 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 337 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 84 records from Roter Berg Werdau (Leubnitz). 25 records from Land and freshwater molluscs of Northern Spain. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 4 records from Microplankton abundance at bottle station SEPT-1999-K2. 3753 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 360690 records from DNV GL Sleipner. 3637 records from University of California Santa Barbara Invertebrate Zoology Collection. 6 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 1057 records from Colección de Laurales, Liliales, Lycopodiales, Magnoliales y Malpighiales del Museo Botánico CORD - IMBIV. 245 records from IRAD Cameroon insect collection. 7561 records from Données chiroptères. 190 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 249 records from Calcareous dinoflagellates nominated in grain fraction > 20 µm. 4 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 50 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 2 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 8 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 363 records from Données du/de la naturaliste Kohn Annie provenant de la base de donnée du SINP Île-de-France CETTIA. 168 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 4196 records from Grand_Site_Sainte-Victoire_2017_12_18. 6 records from On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 113 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 45 records from Averages and ranges of paleoenvironmental proxy records of ODP Hole 108-658C (Table 1). 57 records from CSIRO Yellow Box Fragmentation Project. 210 records from Nannofossil abundance of Hole 94-610B. 15193 records from Entomology Collection at the Natural History Museum of Utah. 20044 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 9 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 1533 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 100 records from Total foraminifera counts of multinet M21/2_MSN644. 41 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (1), 2009 - Données faune. 169717 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 4 records from Symphyla Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 65458 records from ALCB - Herbário Alexandre Leal Costa. 138 records from (Table 7) Dinoflagellate cyst species distribution in ODP Hole 112-680B. 114 records from BIRDRACE LiLaLau. 3209 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 23965 records from Fish specimens of Kagoshima University Museum. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 2 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 1 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 547 records from UTEP Invertebrates (Arctos). 66 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 2278 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 1 records from The Phalacridae (Coleoptera, Cucujoidea) of Canada: new records, distribution, and bionomics with a particular focus on the Atlantic Canadian fauna. 418 records from Mamíferos voladores y no voladores del suroccidente colombiano. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 2055247 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 15632 records from Canadian Lakes Loon Survey. 7 records from Two New Species of Composetia (Annelida: Nereididae) from Small Estuaries in the Ryukyu Islands, Southern Japan, with a List of All Species Currently Belonging to Composetia. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 798 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 6921 records from Xylophaga in situ Eclusion Experiment. 176 records from Alan Wormington Collection. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 173 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 2 records from University of Saskatchewan. 1 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 642 records from Protistan plankton diversity along salt gradient. 179 records from Relative abundances of benthic foraminifera in surface sediments (Table A3). 4617 records from Inventaire de la flore du Grand Poitiers 2009. 33 records from Waldstück am Schullandheim Bad Bederkesa. 3240 records from Polish gene bank – passport data of plants accessions which are important in human life. 22 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1459 records from M. Gollop Collection. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 185 records from SMDB - Santa Maria Departamento de Biologia. 1 records from Données naturalistes d'Olivier DELZONS. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 1 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 94 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 3 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 787 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 16071 records from (Appendix 4) Distribution of benthic foraminifers, living, dead, and total assemblage counts, and faunal diversity in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 32 records from Caracterización Floristica del Paramo de Frontino o del Sol. 1831 records from Modelaje de la Distribución geográfica de Pinus pseudostrobus y P. leiophylla. 845 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 85 records from Birdrace-Die_Paradiesvögel-Herford. 3 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 11 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 5 records from Plathelminthes - SMF. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 1545 records from NatureMap Calcrete Survey. 466 records from Benthic foraminifera counts of sediment core PS1852-2. 2718 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 6642 records from Distribution of foraminifera of sediment core GIK23258-2. 10017 records from Insect specimens of Rikuzen-Takata City Museum. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 712 records from Cowan Tetrapod Collection - Mammals. 1257 records from Actualización de la información sobre los maíces criollos de Oaxaca. 2 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 28 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 27 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 8 records from The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae). 183 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 947 records from Phytoplankton abundance in surface water in May 1996, Pisco, Peru. 7 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 12343 records from University of Minnesota Insect Collection. 249515 records from ARABEL - Arachnologia Belgica. 40215 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 532 records from (Table 6) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 2848 records from Tableaux de prélèvements communaux. Réseau Ongulés sauvages ONCFS-FNC-FDC. 11968 records from Arctic Species Trend Index (ASTI) : Marine. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 1671 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 5184 records from Fungi on beech (Fagus sylvatica) wood, Halland, Sweden. 2599 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 32271 records from Wolli Creek Preservation Society Bird Survey. 588 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 8932 records from LSUMZ (LSU MNS) Fishes Collection. 385 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 4 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 6 records from 2. Donauinsel bei Entau. 18 records from Nano and microzooplankton abundance and biomass at station NBP97-01-02-2. 1 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Wiese am Waldrand (Gurtweil). 4 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 39 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 405 records from Planktic foraminifera assemblage in sediment core GIK17050-1. 5 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_04_2017_12_18. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 243 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 6338 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 86 records from SEWBReC Springtails and allies (South East Wales). 759330 records from Collation of spatial seagrass data from 1984 - 2014 for the Great Barrier Reef World Heritage Area (GBRWHA) (NESP TWQ 3.1, TropWATER, JCU), Australia (1984-2014). 2076 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_12-CTD147. 28934 records from Pacific Reef Assessment and Monitoring Program: Rapid Ecological Assessments of Fish Large-Area Stationary Point Count Surveys (SPC) at Coral Reef Sites across the Pacific Ocean from 2000 to 2007. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 749 records from Carabidae of Wales and England. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 71848 records from The Himalayan Uplands Plant database (HUP Version 1). 8 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 148143 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 18 records from UWYMV Herpetology Collection (Arctos). 52 records from Dinoflagellate cysts from sediment core PS2757-8. 46 records from Liether Park (LMS), 5a. 11873 records from Midden-Limburg Fish Ponds Survey. 19848 records from Herbarium (ICEL). 25777 records from Herbarium Senckenbergianum (FR) - Fungi. 1825 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 1 records from New species, redescriptions and a new combination of Acanthocyrtus Handschin, 1925 and Amazhomidia Cipola & Bellini, 2016 (Collembola, Entomobryidae, Entomobryinae). 252 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 179 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 3 records from A new species of the ant genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae) from the Caribbean region. 4 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 898 records from Kyklades-data of the Central Aegean Sea. 15870 records from RNF - Données de la Communauté de Communes de Gevrey Chambertin. 892 records from Geometridae de France métropolitaine. 3685 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 82 records from Cactophilic Drosophila and Opuntia. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 2 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 3442 records from Inventario de corales pétreos, asteroideos, equinoideos y peces óseos de arrecifes de la costa de Jalisco, Colima y Michoacán. 2829 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 158 records from Planktic foraminifera counts at CTD station PS55/063. 22502 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 12 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 203 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 3862 records from Leicestershire and Rutland Aculeate Records. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 7115 records from Sistematización del Herbario Nacional Forestal Biól Luciano Vela Gálvez. 136 records from Oberes Schindelbachtal. 407 records from Megafaunal data from the 2009 BIOFUN trans-Mediterranean deep-sea cruise. 105717 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 16 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 370 records from Size of planktic foraminifera at CTD station PS55/051. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 120 records from Whale catches in the Southern Ocean. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 2 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 24 records from Benthic macrofauna abundance of sediment core 13200-008. 2 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 67958 records from The 6-7th National Survey on the Natural Environment: Vegetation Survey. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 282 records from (Table 2) Distribution of some benthic foraminifera in ODP Hole 108-658A. 1 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 7081 records from Eurobodalla Regional Botanic Gardens. 25744 records from CABI Africa Invasive and Alien Species data. 30742 records from River Biologists' Database (EPA). 3 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 76538 records from Tiroler Landesmuseum Ferdinandeum. 75 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 38 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 868 records from Colección de Mamíferos del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-M). 8319 records from Epibenthos and demersal fish monitoring at long-term monitoring stations in the Belgian part of the North Sea. 24784 records from National Mammal Atlas Project, online recording. 491 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 335 records from Range table from benthic foraminifers in ODP Hole 198-1209A. 430 records from Benthic foraminifera counts of sediment core GIK23351-1. 1 records from Hydaticus (Prodaticus) hauthi sp. nov., a new diving beetle from the cloud forest in the Cordillera El Sira, Peru (Coleoptera: Dytiscidae). 19 records from Benthic macrofauna abundance of sediment core 13077-063. 8804 records from Odonata records from RSPB Reserves 1970-2009. 1802 records from Diatomeas bentónicas de los oasis de Baja California Sur. 4143 records from WII Herbarium Dataset. 515 records from Données supplémentaires Atlas des Mammifères marins. 1 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 2200 records from Quaid-i-Azam University Herbarium. 91 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 7 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 18 records from Anfibios presentes en el Cerro Jánano. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 7263 records from COLETA - IMAR/DOP-Uac reference collection from 1977 to 2012. 160 records from Abundance of radiolaria at station UT99-23-2. 1553474 records from NBIS Records to December 2016. 1 records from A new species of cascade frog (Amphibia: Ranidae) in the Amolops monticola group from China. 48 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 74-527. 101 records from Nezara viridula records held by the Royal Horticultural Society. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1677 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 2661 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 277 records from Assemblage of living benthic foraminifera in sediment core GeoB3713-1. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 375 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 275 records from South American Antarctic Marine Biodiversity Literature. 3 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 1 records from Description of two new species of Magnispina and a new hypothesis of phylogenetic relationships for Heteropachylinae (Opiliones: Laniatores: Gonyleptidae). 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 3 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 4930 records from SPC PROCFish/C Invertebrates Observations Papua New Guinea 2006. 1001 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 1479 records from Epiphytic mosses from the northwest Iberian quadrant (Spain). 433 records from Specimen references on the Rubiaceae family held by theTAN Herbarium. 17 records from Thirteen new records of ferns from Brazil. 369 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 15 records from Meiofauna abundance in sediment core 54301-010. 2 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 26 records from A new species of the genus Watsonidia Toulgoët, 1981 (Lepidoptera, Erebidae, Arctiini): example of polymorphism in the Amazon of Peru. 1305 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4400 records from Distribution of planktic foraminifera of sediment core M35027-1. 3920 records from (Table 5) Distribution of Pleistocene to late Oligocene nannofossils in ODP Hole 108-659A. 15813 records from FKSE-Herbarium of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 164 records from Abundance of planktic foraminifera at CTD station M39/4_352CTD-11. 8621 records from NE Scotland other invertebrate records 1800-2010. 2 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 856 records from SEWBReC Fish (South East Wales). 1931 records from Datos de ocurrencia de triatominos americanos del Laboratorio de Triatominos del CEPAVE (CONICET-UNLP). 14 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 5 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 22054 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 5836 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 612 records from Deep-sea meiobenthos at Calvi (Corsica) sampled in September 1982. 73 records from Données opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from Bemerkenswerte Faltenwespen aus der äthiopischen Region. Teil 14 (Hymenoptera, Vespidae, Eumeninae). 211 records from (Table 1) Middle Eocene silicoflagellates from DSDP Hole 95-612. 1110 records from FFH-Gebiet "Calwer Heckengäu". 186 records from Naturalis Biodiversity Center (NL) - Crustacea. 813 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE233. 2141 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 1 records from Brown algae specimens of Komatsu City Museum. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 1 records from Ecological Guild Evolution and the Discovery of the World’s Smallest Vertebrate. 75294 records from Bob Merritt Coleoptera Dataset. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 78 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 314 records from Computarización de la Colección de Referencia de Nemátodos Fitopatógenos del Centro Nacional de Referencia Fitosanitaria de la Dirección General de Sanidad Vegetal. 2 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 177 records from Component analysis of TV-guided grab sampler GeoB10071-5. 6858 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 3 records from Contribution to the Mesochorinae (Hymenoptera, Ichneumonidae) of Nepal. 856 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 760219 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 43 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 411532 records from DATAVES. 34 records from Projet Diable de mer - AILERONS. 295 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 5 records from Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae). 27 records from (Table S2) Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 161-975D. 884 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 28 records from Caracterización de la fauna del páramo del Duende, litoral del San Juan, Chocó. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 2 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 622 records from The Broward College Insect Collection. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 135 records from Planktic foraminifera abundance of Hole 73-524. 62 records from Total foraminifera counts of multinet M10/2_MSN229. 2 records from Berea College, Ralph L. Thompson Herbarium. 1 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 16 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 424 records from Distribution of nanoplankton at trap WR2. 103 records from Schwanseepark (87645 Schwangau). 9653 records from Ecosphère_2017_12_18. 4520 records from Données d'observation de la mégafaune marine issues des campagnes océanographiques en France métropolitaine. 382 records from Chronicle of Nature - Phenology of Plants of Bryansk Forest Nature Reserve. 6 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 114 records from BIRDRACE VIE will rock you!. 84 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 56546 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 574 records from Isle of Wight non-native invasive species. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_3-CTD37. 14331 records from Macrophyte Lake Data. 2 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 326 records from Weber State University Herbarium. 1646 records from Données du Busard de Maillard (Circus maillardi) du Parc national de La Réunion. 6958 records from Siliceous microfossil occurrence, Site 177-1091. 4982 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 12384 records from Données du naturaliste Julien Birard provenant de la base de donnée du SINP Île-de-France CETTIA. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 391 records from Range table from benthic foraminifers in ODP Hole 192-1183A. 882 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 636 records from Range table from benthic foraminifers in ODP Hole 149-900A. 5 records from Bees of the family Halictidae Thomson, 1869 from Dominica, Lesser Antilles (Hymenoptera: Apoidea). 117 records from Streuobstwiese Stedar 2009. 149 records from Total foraminifera counts of multinet M21/2_MSN640. 8 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 57 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 81 records from Kystfuruskoger i Tysnes og Fusa. 767 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 19 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 98 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 1326 records from Sistematización de la colección de peces del centro de México. 445 records from Estudio ecológico-florístico de los enclaves de vegetación xerofítica inmersos en una selva baja caducifolia en el Istmo de Tehuantepec, Oaxaca. 91 records from Diatom abundance of Hole 95-613. 5 records from UCLA Donald R. Dickey Bird and Mammal Collection. 1435 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 40 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 14 records from Results of palynological analysis of Hole 302-M0004C. 7 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-09-1. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 135 records from Globigerinita spp. in sediment core MSM05/5_712-2. 7261 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 60 records from University of Vermont, Pringle Herbarium, Algae Collection. 23 records from Abundance of benthos infauna at station GIK23042-2. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 68 records from Streuobstwiese. 396 records from (Table AT9) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134B. 3 records from The Onthophagus fuscus (Coleoptera: Scarabaeidae) species complex: an update and the description of a new species. 2220 records from Données LPO Réserve naturelle régionale du marais de la Vacherie. 44 records from Description of lithologic section units of IODP Hole 325-M0041A. 3622 records from SIM-Fungal records compiled by Joan Montón. 2714 records from Plant specimens of Obihiro Centennial City Museum. 304712 records from Western Australian Museum provider for OZCAM. 1152 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 84 records from Range table from benthic foraminifera in ODP Hole 199-1220A. 3917 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 690 records from Benthic foraminifera counts of sediment core GIK23352-3. 4510 records from Carabidae of the Carpathians. 3644 records from Estudio taxonómico distribucional de los peces del estado de Chiapas, México. 14772 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 12007 records from Données Entomologiques A. HORELLOU 1988-2018. 389 records from Antarctic and SubAntarctic Ophiuroidea - MNA (Section of Genoa). 65 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 558 records from Foraminifera abundance of Hole 74-526A. 267 records from Dinoflagellate abundance of Hole 81-555. 14 records from Distribution of planktic foraminifera of sediment core GIK23062-1 at stadium 5.5. 6858 records from Benthic foraminifera abundance in per cent of Hole PRAD1-2. 30 records from Geführte Wanderung im Eselsbachtal. 46 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 9 records from Données opportunistes amphibiens-reptiles du Nord et du Pas-de-Calais. 797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 1686 records from Herbier National de Guinée (HNG). 3 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 455 records from EDIT - ATBI in Gemer area (Slovakia). 18382 records from Global compendium of Aedes albopictus occurrence. 1 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 8300 records from données aranéologiques de LEDOUX Jean-Claude. 88 records from Teich Berlin Wuhlheide. 10 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 637 records from Counts of the living benthic foraminifera assemblage in surface sediments of the North Atlantic. 150 records from AKG-Gelände (Bensheim). 531 records from Pollen analysis of sediment profile NMS0 from Neumühler See. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 2 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 12 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 2. 138 records from Total foraminifera counts of multinet POS247/2_MSN1380. 2088 records from Données des collections d'algues du MNHN. 59 records from Phytoplankton abundance at station Casma_2003-02-27_2, Casma, Peru. 3190 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 1916 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 578 records from Coléoptères Silphidés du département du Loiret. 71 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 2356 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 104 records from Urwald 1 (Bad Waldsee). 326930 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 2 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 959 records from Nannofossil abundance of Hole 74-526A. 122 records from Birdrace-Hügelland-Mainz/Bingen. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 9 records from Hazel Dormouse in Ireland. 409 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/18. 285 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 4 records from Description of a new Aemene Walker, 1854 from North Thailand and Myanmar, with a checklist of the genus (Lepidoptera, Erebidae, Arctiinae). 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 1776 records from Colección de Bruniales, Buxales, Canellales y Caryophyllales del Museo Botánico CORD - IMBIV. 26 records from Nanoplankton abundance at station GeoB2017-4. 588 records from Agroforestry plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 30 records from A New Species Of Apostenus From California, With Notes On The Genus (Araneae, Liocranidae). 6 records from Revision of the Ulopinae leafhoppers (Hemiptera: Cicadellidae) of the Indian subcontinent, I. Ulopini genera: Daimachus, Radhades and Ulopsina. 123 records from Total foraminifera counts of multinet M21/4_MSN694. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 24385 records from Insects, Outer Hebrides. 190 records from Abundance of meroplankton during cruise BP00 (southern Kara Sea). 84 records from Range table from planktonic foraminifers in ODP Hole 169-1035A. 3 records from Description of eight new species of the traumatically inseminating plant bug genus Coridromius (Heteroptera: Miridae: Orthotylinae: Coridromini). 220 records from Mammals in MZNA-VERT: project Loza. 46 records from An der Ohm, (Wettsaasen). 49 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 185 records from Inventaire des odonates d'intérêt communautaire. 79 records from Plasm bearing foraminifera counts of multinet M26/1_MSN844. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 77 records from Nannofossil abundance of Hole 73-521A. 891 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 7427 records from BioGIS - Vascular plants - Israeli Gene Bank. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 4 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 612 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 5 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 207 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 16119 records from marine metagenome Metagenome. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 118 records from Radiolaria assemblage in sediment core GIK23400-3. 877 records from Range table from benthic foraminifers in ODP Hole 151-913B. 10 records from Sea Education Association Sargasso Sea Cruise C247 May 2013. 647 records from Invertebrates (except insects), Outer Hebrides. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 52 records from New species of Cirratulidae (Annelida, Polychaeta) from abyssal depths of the Clarion-Clipperton Fracture Zone, North Equatorial Pacific Ocean. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 79 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 1835 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 2102 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 2618 records from E. C. Smith Herbarium (ACAD) - Cape Breton University Collection. 2 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 62 records from Sibojaï_2017_12_18. 774 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 277 records from Inventaire de la faune malacologique de la Réserve naturelle des gorges de l'Ardèche (2002). 1080 records from DBRC Lutra lutra records 1952 - 2016. 10 records from Mammalians Specimens of Akita Prefectural Museum. 32 records from New records for Albania based on taxa from the Prespa National Park. 14479 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 732 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 1 records from Description of a new Oriental stonefly species, Phanoperla constanspina (Plecoptera: Perlidae) from Mindanao, Philippines and association of life stages using DNA barcoding. 29429 records from Abondances et caractéristiques biologiques des juvéniles de saumons échantillonnés lors des indices d'abondance du saumon dans la rivière Scorff (France). 1007 records from Los mamíferos del estado de Durango, México. 5063 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 119 records from Occurrence data of some marine invertebrates and freshwater crabs housed in the natural history collection at the National Museums of Kenya. 7 records from New species of Xiphoniscus and new record of Androdeloscia escalonai (Isopoda, Scutocoxifera, Oniscidea, Philosciidae) from Brazilian Amazon. 1327 records from Observations opportunistes de mammifères marins de l'observatoire PELAGIS. 91063 records from MSB Fish Collection (Arctos). 6 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 266 records from Ostracoda abundance of Hole 95-612. 59 records from Schulteich Freie Waldorfschule Darmstadt. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 107 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 2 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 4 records from Four new species of terrestrial-breeding frogs of the genus Phrynopus (Anura: Terrarana: Craugastoridae) from Río Abiseo National Park, Peru. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 13837 records from AMNH Bird Collection. 22052 records from CNIN/Abejas de México/Apoidea. 1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 492 records from Données du/de la naturaliste Chevallier Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 1006 records from Flora útil del Municipio de la Huerta, Jalisco. 3233 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 108 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 3 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 878 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 2134 records from Kurzflügler_Raw1. 871 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 1005 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 159 records from Total foraminifera counts of multinet M36/6_MSN1196. 14 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 2189 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 8 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 11013 records from RECORD Bryopsida Data. 140 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 7 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 12 records from Art´n Vielfalt im Kinderwald. 47 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 3876 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 23 records from Benthic macrofauna abundance of sediment core 13077-093. 65 records from Invasive Non-Native Species, Outer Hebrides. 251794 records from Phase 2 Lowland Grassland Survey of Wales. 4 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 5904 records from Suivi Temporel des Libellules (STELI). 11 records from Nano and microzooplankton abundance and biomass at station NBP97-01-25-2. 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 31410 records from WCPS Bird Survey Project. 106 records from Sylter Meerstrandläufer. 862 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 78170 records from First Bird Atlas. 2 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 25141 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 61 records from Relative abundance of coccosphere-units of sediment core GIK23071-2. 5406 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 4 records from Ensemble des données Orthoptères. 1 records from Pseudaeginella telukrimau sp. n., a new species of caprellid (Crustacea: Amphipoda) from Malaysia. 12 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 65 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 12 records from Range table from planktonic foraminifers in ODP Hole 151-912C. 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 1342 records from BSM marine Targeted Locus. 17 records from Données naturalistes de Franck MERLIER. 199 records from Total foraminifera counts of multinet M10/2_MSN218. 1748 records from (Table 9) Distribution of planktonic foraminifers in ODP Site 112-687. 907 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 2808 records from Natura 2000 Vallée de la Seille. 2256 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 7129 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 6909 records from Inventario de Hymenóptera; parasítica en México. 528 records from UAM Herbarium (ALA), Algae Collection (Arctos). 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 47575 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 3 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 8435 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 624 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 569 records from Benthic foraminifera abundance of Hole 84-567A, Part 2. 1187 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 91 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 247 records from Données de la structure ANCA (les Amis Naturalistes des Coteaux d'Avron) provenant de la base de donnée du SINP Île-de-France CETTIA. 705 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 11 records from Meiofauna abundance in sediment core 13368-015. 2637 records from Jeu de données de la Société limousine d'Etude des Mollusques. 76 records from BIRDRACE Nachtigallen. 286 records from schulgarten. 183 records from Sistemática y biogeografía del género Reithrodontomys (Rodentia: Muridae). 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 4 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 2069 records from Stable oxygen isotope ratios of foraminifera from late middle Eocene sediments of ODP Site 171-1052 from Blake Plateau, West Atlantic Ocean (Appendix). 21 records from Tauchen und Meer 02. 292 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 2 records from Données naturalistes de THÉVENOT Jessica. 2 records from Sediment properties of core CD86_09_PC. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 1 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 234 records from Lucanidae. 2661 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé t du Plateau. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 25443 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 2 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 56 records from Birds Specimens of Akita Prefectural Museum. 6 records from Urochordeumatidae Silvestri, 1909, a millipede family endemic to Washington State, USA (Chordeumatida, Striariidea, Striarioidea). 2609 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 20929 records from TWIC Biodiversity Field Trip Data (1995-present). 1 records from A New Species of Abbrosoga (Hemiptera: Fulgoroidea: Delphacidae), An Endemic Puerto Rican Planthopper Genus, with an Updated Checklist of the Delphacidae of Puerto Rico. 353 records from Range table from benthic foraminifers in ODP Hole 159-959D. 17 records from Range table from benthic foraminifers in ODP Hole 177-1088B. 5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 20753 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Gill Net. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 333 records from Langes Tannen (Uetersen). 88 records from Total foraminifera counts from M35/1_MSN1065. 2176 records from Marine Turtles. 314 records from Content of different diatom species in sediment core GIK23259-2. 1215 records from Churchyards for London. 511 records from Range table from planktonic foraminifers in ODP Hole 151-910C. 511 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 8 records from Aktion des Romain-Rolland-Gymnasiums. 329 records from Chronicle of Nature - Phenology of Fishes of Sikhote-Alin State Nature Biosphere Reserve Named After K. G. Abramov. 127 records from Total foraminifera counts of multinet M21/2_MSN650. 6 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 6866 records from VIT Herbarium - Mycotheca (The Natural History Museum of Álava). 8 records from Vermont Orthoptera Records from Historic Dot Maps. 6 records from A new species and new records of Oocyclus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil. 159 records from Nannofossil abundance of Hole 67-499B. 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 343 records from Observations de cétacés à partir de navires de pêches: campagnes PETRACET/PROCET et OBSMAM - Observatoire PELAGIS. 1 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 2725 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 2 records from Moenkhausia restricta, a new species from the upper Rio Negro, Amazon basin, northwestern Brazil (Characiformes: Characidae). 417 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 386 records from Benthic foraminifera counts of sediment core GIK17730-4. 19 records from Four new species of Paranaitis Southern, 1914 (Phyllodocidae, Annelida) from southern and southeastern Brazil. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 22728 records from Restauración y conservación de Isla Guadalupe. 9280 records from (Table 1) Stratigraphic occurrence of selected diatom species from ODP Hole 105-647A. 21443 records from Banksia Atlas. 1544112 records from SA Flora (BDBSA). 12 records from Coleção de Coleoptera da Universidade de Brasília. 2183 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 98 records from Warnowtal (Rostock). 972 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 2 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 2171 records from Marie-Victorin Herbarium (MT) - Bryophytes. 23 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 315 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 196820 records from National Benthic Inventory. 296 records from Marine Non Native Species records from Natural Resources Wales (NRW) Monitoring Research and Ad-hoc Sightings. 8 records from Phenological Center - Fishes (Murmansk). 194 records from Small rodents trapped in old growth forest in Vegårshei, Norway. 1 records from On the taxonomy of the subgenera Cyabarda Karisch, 2013, Idiovulpecula Karisch, 2013 and Paravulpeculella Karisch, 2013 of the genus Cyana Walker, 1854, with descriptions of three new species from Africa (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 181 records from Dinoflagellate cysts from sediment core PS1295-4. 111 records from BIRDRACE Die Wendehälse. 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 542 records from Planktic foraminifera abundance of Hole 68-503A. 33 records from (Table 2) Documentation of vital effect change in Coccolitophorides above the FAD Emiliania huxleyi in DSDP Site 90-594 east of South Island, Southwest Pacific. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1148 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 186 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 1 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 6078 records from Scotland Otter Survey Database. 11 records from Fiocruz/CAVAISC - Coleção de Artrópodes Vetores Ápteros de Importância em Saúde das Comunidades. 12449 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 35 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 3436 records from Biodiversité marine de l’île de La Réunion. Programme BIOLAVE. 953 records from Utah State University, Intermountain Herbarium. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 132579 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 104 records from Caracterización Florística de un Área Degradada por Actividad Minera en la Costa Caucana. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 47 records from Baltic Sea Basin sediments diversity Raw sequence reads. 816 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 8316 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: complementary work sites [2010-2014]. 14325 records from Mammalogy Collection - Royal Ontario Museum. 2595 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 101 records from Total foraminifera counts of multinet POS231/3_MSN1335. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 9284 records from Seasearch Marine Surveys in the Isle of Man. 31 records from Microzooplankton abundance and biomass at station TT045_2-1. 222 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 21495 records from CAS Entomology (ENT). 162 records from Range table from planktonic foraminifers in ODP Hole 182-1132C. 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 181351 records from Carnet B Lorraine. 1874 records from Naturalis Biodiversity Center (NL) - Pisces. 28 records from Range table from planktonic foraminifers in ODP Hole 170-1039A. 24 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 444 records from Phytoplankton abundance in surface water in October 1996, Chimbote, Peru. 119 records from Nannofossil abundance of Hole 74-526C. 2425 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 3 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 589 records from Radiolaria assemblage in sediment core GIK23414-6. 377 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 287 records from Myxomycetes collection of the University of Eastern Finland. 44 records from Enquête participative "Lichens forestiers d'Auvergne et du Massif Central". 1248 records from Données naturalistes d'Emmanuel SECHET. 23276 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 210957 records from Seasearch Marine Surveys in England. 8 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 38 records from Planktic foraminifera abundance of Hole 84-566C. 43 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 22 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1337. 1 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 770 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 789 records from Collection Trichoptera - SMF. 8 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 20 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 3281 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 1 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 3776 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 22273 records from Arizona State University Hasbrouck Insect Collection. 306 records from Invasive Alien Species Occurrence in Ghana. 54555 records from CCAMLR historic KRILL. 2 records from Taxonomy of the Myrmicine ant genus Temnothorax Mayr, 1861 (Formicidae: Myrmicinae) in the Arabian Peninsula. 23 records from Benthic foraminifera abundance of Hole 93-603. 2 records from Range table from planktonic foraminifers in ODP Hole 141-862B. 160 records from Données espèces - Expertise IPE 37. 1004 records from Nannofossil abundance of Hole 74-528A. 11707 records from Recensement des espèces en vue de l'élaboration du répertoire des forêts sacrées, forêts galeries, savanes et autres formation floristique du Bénin.. 3973 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 251 records from (Table 3) Distribution of benthic foraminifers in middle Miocene sediments of ODP Hole 182-1126B in the Great Australian Bight. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 1592 records from Millenium Seedbank (MSB). 154 records from Shannon Index and species richness for arthropods. 21870 records from Online Atlas of Vascular Plants 2012-2020. 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 159 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 2023 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 10258 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 1 records from Revision of the Diplommatinidae (Gastropoda: Cyclophoroidea) from Java. 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 61762 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 6 records from Abundance of two benthic foraminifera species in sediment core 12930-007. 1355 records from Phenological Center - Plants (Laplandskiy). 2 records from Revision of Scelio pulchripennis - group species (Hymenoptera, Platygastroidea, Platygastridae). 12 records from Crustacea ZMK. 21 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 53 records from Results of foraminifer and ostracode analyses of Hole 302-M0002A. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 858 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 3 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 778 records from Benthic foraminifera abundance of Hole 84-567A. 210 records from Lebensraum Gesamtschule (Langerwehe). 429 records from Foraminifera abundance of Hole 64-481. 3841 records from ICEL (Land - Invertebrates). 9 records from Sarcodine counts and carbon biomass at station TT008_4-PMOC1. 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 9690 records from UTEP Herpetology (Arctos). 8628 records from Biological Reference Collections ICM CSIC. 94 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 3272 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 10 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 13 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 240 records from Chironomid remains in the sediment sequence of Site PG1212. 1364 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3379 records from Lista florística de la Costa Grande del estado de Guerrero. 10 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 81895 records from MDFRC macroinvertebrate survey. 168 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 62 records from Amtsrain Apolda-Zottelstedt. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 179 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 62122 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 4 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 57 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 24985 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 9476 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 98 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 26 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 99 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 152 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 61 records from Shrews of Poland. 5914 records from K-State Museum of Entomological and Prairie Arthropod Research. 370 records from Otter survey of Ireland 2004 & 2005. 1039 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 9968 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 3 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 85774 records from Suivi Temporel des Rhopalocères de France (STERF). 8 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 1552 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 144 records from Total foraminifera counts of multinet POS247/2_MSN1386. 23 records from Landwehrbach. 6 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 17 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 602 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 9781 records from CSIRO, fish surveys by the Soela, 1980s. 38 records from Données de VINCENT Alexis (SAPROX). 406 records from Nannofossil abundance of Hole 78-543. 6926 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 3 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from Total foraminifera counts of multinet FCA97C_MSN1339. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 5896 records from University Of Pretoria: Lacewing Database Project (1911-2015). 2630 records from USAC Mammals Collection. 383 records from Nannofossil abundance of Hole 66-490. 165 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 205 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 111 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 2711 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 733 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 78 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 270 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 2252 records from Données naturalistes de Bernard Lalanne-Cassou. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1136 records from Nannofossil abundance of Hole 82-558A. 1513 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 617 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 2 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3320 records from BioGIS - Mammals - SPNI. 11 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 90159 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 28365 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 216 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 582939 records from SEWBReC Birds (South East Wales). 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 154 records from Total foraminifera counts from multinet SO119_MSN1285. 226 records from Collection Echinodermata SMF. 1 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 4132 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 1570 records from MEXU/Flora de Oaxaca. 10453 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 625 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 5593 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 167 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 287 records from Nannofossil abundance of Hole 66-488. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 72 records from Heavy minerals of sediment core PL94-64. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 101185 records from Amphibiens et Reptiles de France (Enquête 2). 1383 records from Dolichopodidae of Portugal - dataset 2009-2018. 3162 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1214 records from Données naturalistes d'Alain BERLY. 15276 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 74 records from Données opportunistes. 1698 records from Red-throated diver national surveys in Scotland - raw data. 2240 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 149 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 249 records from Inventaire et regroupement de données Natura 2000. 7145 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 180706 records from Données de la flore d’Alsace (SBA). 490 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3668 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 139 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 1 records from Données naturalistes de Caroline DAGNEAU. 2 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 2 records from A new species of Hemigrammus Gill 1858 (Characiformes: Characidae) from the upper Rio Negro, Amazon basin, Brazil. 447 records from Banco de Germoplasma de Especies Nativas del Instituto de Ecologia y Ambiente Humano - UNSA- Arg. 26 records from Range table from ostracoda in ODP Hole 160-967A. 178 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 4 records from Description of Brachymeria philornisae sp. n. (Hymenoptera: Chalcididae), a parasitoid of the bird parasite Philornis trinitensis (Diptera: Muscidae) in Tobago, with a review of the sibling species. 123 records from City of Edinburgh Natural Heritage Service - Hillend Wildflower Meadow Survey. 101 records from Naturgrundstück (Eutin). 4275 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 390 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 9 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 1319 records from Odonata de la huasteca potosina (insecta). 19 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 226 records from données araneologiques de LEENKNEGT Virginie. 156 records from (Appendix) Relative abundance of some calcareous nannofossils in ODP Hole 119-738C. 1 records from The myth of monophagy in Paralobesia (Lepidoptera: Tortricidae)? A new species feeding on Cypripedium reginae (Orchidaceae). 3 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 179 records from Checklist of rust fungi (Pucciniales) occurring in Portugal. 12488 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 3 records from Two new species of Parandrinae (Coleoptera: Cerambycidae) in the genera Parandra and Acutandra from South America. 110 records from Données naturalistes de Mr MONTAGNER Sylvain. 1580 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 37 records from Plasm bearing foraminifera counts of multinet M27/2_MSN879. 42 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 46365 records from Données de l'Observatoire de la Faune de Bourgogne. 1184 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 33 records from Planktic foraminifera assemblage in sediment core GIK23074-3. 822 records from (Table 1) Relative abundances of benthic foraminifera in ODP Hole 117-725C. 2 records from Osmiine bees of the genus Haetosmia (Megachilidae, Osmiini): biology, taxonomy and key to species. 32 records from Analyses of the recent components of sediment core PS1402-2. 2712 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 124 records from Total foraminifera counts of multinet POS247/2_MSN1388. 41 records from Descriptions of two new species of Brachyzapus Gauld & Dubois (Hymenoptera: Ichneumonidae: Pimplinae) from South Korea with key to a Palaearctic species. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 2 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 56 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Echinodermata. 938 records from (Appendix D) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748C. 97 records from Phenological Center - Birds (Murmansk). 353 records from Benthic foraminifera accumulation rate and benthic foraminiferal productivity proxies at ODP Site 165-999 in the Caribbean (Appendix A). 9 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 39 records from Range table from planktonic foraminifers in ODP Hole 180-1112A. 1207 records from Microbial diversity studies of Arabian Sea sediment. 4142 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 123 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 18 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 153 records from Echinoderms from the Seaflower Biosphere Reserve. 300 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 72279 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 23 records from Analyses of the recent components of sediment core PS1011-1. 122 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/562-1. 33507 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 19 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 13519 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 593 records from Mamíferos voladores laguna El Tinije. 23 records from (Table 1) Distribution of palynomorphs in ODP Hole 123-765C. 221 records from Mission ONF 2008 d'inventaire de la Réserve naturelle de la Trinité. 92 records from Birkenloh. 448 records from Species observations during citizen science expeditions. 4 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 346 records from Coleção Entomológica Moure e Costa. 1500 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Day/night stratified zooplankton sampling onboard the Norwegian R/V Jan Mayen. Program ALV. 17 records from MVZ Herp Observations (Arctos). 103 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100260. 324 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 181 records from Collection Cnidaria fossil SMF. 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 459 records from NSG Karwendel. 871 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 182 records from Données naturalistes d'Olivier LAURENT. 80 records from Total foraminifera counts of multinet M12/3_MSN562. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 18159 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 58 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 91 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 2744 records from Distribution of major planktic foraminifer at Site 177-1090. 128 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 126 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 88220 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 17 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 2 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 4644 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 1139 records from SWECO. 4227 records from Données naturalistes de Loïc SALAUN. 13871 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 1762 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 754001 records from Flore Franco-Belge. 10809 records from EAC - Herbário Prisco Bezerra. 2507 records from East Ayrshire Species Database. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 1200 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 9 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 1486 records from Leif Richardson Vermont Bee Specimens. 3 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 2 records from Planktic foraminifera counts of multinet PS2616-5. 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 4207 records from CASES2003_2004. 374 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 33713 records from Fife Nature Records Centre combined dataset. 3 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 4 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 17 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 31 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 3069 records from Odonata de Veracruz. 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 270 records from BIRDRACE Niederlausitz-Team. 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 324 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 281 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 3682 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 82 records from CG04_2017_12_18. 1672 records from Composition of the coccolith flora in sediment core GeoB1710-3. 339 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 185 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 3 records from Collection Ephemeroptera - SMF. 530 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 33 records from Microzooplankton abundance and biomass at station TT045_15-2. 7083 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 66964 records from Denver Museum of Nature & Science - Entomology. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 84 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 14473 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 6745 records from Database for alien invasive plants occurrences in Germany. 9 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 34 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 884 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1330 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 2714 records from 成龍溼地鳥類生態紀錄. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 84 records from Benthic foraminifera abundance of Hole 84-566C. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 2 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 2572 records from OUPR - Herbário "Professor José Badini". 10 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 50872 records from National Biodiversity Data Bank. Observation records, 1900-2014. 304 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 6 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 11826 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 92 records from Nottekanal, Klasse 7 - 10. 36 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 19 records from Amoeboid protists isolated from ancient Siberian permafrost. 1821 records from Inventaire des Mollusques Sphaeriidae de France. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 14634 records from données aranéologiques de CORNIC Jean-François. 25 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 78 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 1761 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1409 records from Diatom assamblage in samples from sediment trap OG5. 1450 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 4528 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 50 records from Flora und Fauna im Brexbachtal. 896303 records from MICROBIS database. 190 records from Herpetofauna laguna El Tinije. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 123 records from Birdrace-Professorenteam-Münster. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 2822 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 235129 records from Swiss National Orthoptera Databank. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 131 records from Planktic foraminifera counts at CTD station PS55/083-1. 42632 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 7762 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 2921 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 20 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 7978 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 661 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 2 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1036 records from BUND - Dassower See (Lübeck/Dassow). 41168 records from Données naturalistes de Monsieur François FOURNIER. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 984 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 53688 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 774 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6067 records from Arthur Chapman Observations. 571 records from Cuxhavener Küstenheiden. 1463009 records from Hatikka Observation Database. 352 records from UWYMV Bird Collection (Arctos). 74 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 96 records from Données naturalistes de Monsieur JOURDE Rémi. 106972 records from inatura - Erlebnis Naturschau Dornbirn. 409 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 5 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 539581 records from PlutoF platform observations. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 1 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 9 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 15 records from Benthic macrofauna abundance of sediment core 13078-015. 46 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 1147 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 150 records from Données Mammifères marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 10075 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 18839 records from WTSWW Data: All Taxa (West Wales). 516 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 40 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 412316 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 195931 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 35 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 5 records from Coccolith counts of multinet M32/5_MSN981. 10 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 16 records from Brock University Herbarium (BU). 220 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 7115 records from Whicher Scarp Flora Survey. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 3 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 89 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 7 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6432 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 154 records from Grand Voyeux - Suivis scientifiques. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 43 records from UWIZM Cnidarians. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 11 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 103445 records from Tasmanian Museum and Art Gallery provider for OZCAM. 21 records from TTRS Mammals. 3 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 45 records from Brown bear monitoring data from Deosai National Park. 267 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 850 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 8 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 91663 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from University of Sindh Jamshoro Herbarium. 2924 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 21 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 20 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1096 records from Registros Primates Neotropicales Convocatoria APC. 2 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 12 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 11 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 5 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 4682 records from La familia Asclepiadaceae en México. 1 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 4 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 25 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 594 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 1 records from Biodiversity Surveys, South-east Arnhem Land. 61 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 624 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 287 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 26 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 5809 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 22 records from Wichita State University Collection. 86 records from Données naturalistes de Pierre-Alexis RAULT. 216782 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 1 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 106 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 5 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 74 records from pbzt_insect_biodiversity. 1 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 217 records from NZCS Upper Tapanahony Expedition 1991. 159 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 2 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 852 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 3 records from DD_cyano Targeted loci environmental. 5 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 53 records from Coleção de Nematoda do Museu Nacional - UFRJ. 6556 records from Inventory of plant species through Benin (West Africa). 553 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 2000 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 2612 records from Fungi specimens of Saitama Museum of Natural History. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 8 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 155 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 224 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 841 records from Planktic foraminifera abundance of Hole 72-518. 33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 372 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 630 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 14 records from Nemertini - SMF. 680 records from Bosque Mesófilo de Montaña de México. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 20206 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 30 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 21 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 1 records from Collection ornithologique A. Maës. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 29 records from Mammal specimens of Komatsu City Museum. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 74 records from ACT and Southern Tablelands Weed Spotter. 41 records from Örtzemündung (Stedden). 19198 records from National Stag Beetle Surveys (Great Stag Hunts). 1989 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 2763830 records from Eremaea. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 14 records from Benthic foraminifera abundance of Hole 96-620. 105 records from Nanoplankton abundance at station GeoB2006-4. 2 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 292 records from Données naturalistes de Monsieur LEFEBVRE François. 28 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 982 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 14 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 23 records from Ackerrain Plönhagen. 4774 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Données odonates. 194 records from Malawi-Histeridae-Biodiversity-Data. 10604 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 249 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 25 records from Microzooplankton abundance and biomass at station TT043_4-1. 313 records from BIRDRACE Gätkes Erben. 2990 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3708 records from Benthos counted on dredged samples during Valdivia cruise VA53. 3 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 4971 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 56 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 117 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 755 records from Carabidae of the European North-East of Russia. 3096 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 6 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4011 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 6 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 1057 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 22 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 6 records from Abundance of benthos infauna at station GIK23065-1. 14205 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 4532 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 2462141 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 59 records from Bishop's University Insect Collection (BUIC). 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 317571 records from BioFokus. 10549 records from Anymals+plants - Citizen Science Data. 830 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 27 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 32660 records from The national database for marine data (MADS). 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 1 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 2327 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 3 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 55 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 1297 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 3444 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1481 records from Leicestershire and Rutland Mature trees Inventory 2011. 362 records from Pollen data of trap CB4. 16 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 18 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 92 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 11 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 54 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 347 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 136 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 384 records from "Schwarzwassertal" bei Pobershau. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 2041 records from marine metagenome Targeted Locus (Loci). 928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 23825 records from Plan de vertebrados de la Patagonia. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 4515 records from Distribution of planktic foraminifera of sediment core M35003-4. 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 148 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 305345 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 57 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 975 records from Danielsberg (Mölltal, Kärnten). 9151 records from LPO_PACA_2017_12_18. 164 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 661 records from Targeting a portion of central European spider diversity for permanent preservation. 216 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 10825 records from Census of species recorded during phytosociological surveys in Benin. 1837 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 1596 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6531 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 7152 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 4582 records from Collection Pisces SMF. 195 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 18234 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 735 records from MEXU/Tipos de plantas vasculares. 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 19 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 444 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 242 records from Landschaftspflegehof (Berlin). 210 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 10 records from Bachpatenschaft Beeke. 84 records from Total foraminifera counts from M35/1_MSN1051. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 11 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 712 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 201 records from Total foraminifera counts of multinet M21/1_MSN606. 3006 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 60 records from Caracterización de la fauna reptiliana asociada a la cuenca del río Atrato, para el estudio de su navegabilidad, Quibdó - Chocó, 2012. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 135565 records from Estonian Nature Observations Database. 10 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 11 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 3 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 29916 records from Botanical Museum, Copenhagen, Mycology Herbarium. 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 6546 records from NCSM Mammals Collection. 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 13 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 855 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 70221 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 152363 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 4 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 991 records from Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 1557 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 473 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 96 records from Total foraminifera counts of multinet M26/1_MSN845. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 4 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 2 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 16560 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 1 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 5 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 7 records from A review of the ant genus Metapone Forel from Madagascar.. 243 records from Thistles species and abundance. 61 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 47 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 2834 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 1 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 2078 records from Flora vascular acuática de la cuenca del Río Tamesí. 15 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 1820 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 17 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 1 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 494 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 507 records from Planktic foraminifera abundance of Hole 84-567A. 1 records from Cladistic analysis and synopsis of Chloropepla Stål (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 1950 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 3 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 3 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 128 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 26 records from Abundance of benthos infauna at station PS1240-1. 110 records from Données du Râle gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 14 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 27 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 12 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 419 records from données arachnologiques de CARR David. 4 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 168 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 477 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 1350 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 3651 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 14448 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 8190 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 134 records from BIRDRACE Griffin Wood Warblers. 261 records from Données espèces -expertise IQE 3. 9 records from Planktic foraminifera abundance of Hole 94-611B. 1736 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 7 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 2 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 396 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 2584 records from Range table from benthic foraminifers in ODP Hole 154-929A. 125 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 3 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 287 records from Données du naturaliste Arnaud Bak. 59211 records from Derek Lott Coleoptera Dataset. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 11150 records from University of Tennessee Bryophyte Herbarium. 1435 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2342 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 6540 records from Likona Invertebrates. 84 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 128096 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 339 records from Amphibiens de Guyane. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 6 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 1186 records from Nannofossil abundance of Hole 75-530A. 6250 records from DBRC Hemiptera species records 1969 to 2015. 38 records from BB-Biodiversität a. 2 records from Collection Myriapoda - SNSD. 1489 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 67356 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1357 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 1954 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 2662 records from Dorset SW Pilot species dataset. 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 20 records from Benthic macrofauna abundance of sediment core 13077-087. 348 records from (Table 2e) Nannofossil distribution chart of petroleum well Leeuwin-1. 154 records from Données de la structure Philofauna provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 2112 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 1 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 11229 records from Cumbria Non Native Invasive Species. 19 records from Inventaire et suivi de la faune écrasée. 596 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 306 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 1 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 1 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 9 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 176 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 371 records from Benthic foraminifera and algae abundance of Hole 81-554A. 1056 records from Diatom assamblage in samples from sediment trap OG4. 150564 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 376 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 217 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 28332 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 90 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 145 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 174782 records from Marine benthic dataset (version 1) commissioned by UKOOA. 329 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 5229 records from European Moth Nights. 8 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 81 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 292 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 723 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 771 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 2 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 2 records from PRA Sonneur à ventre jaune - étude de répartition. 260 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 1242 records from Collection Crustacea - ZMB. 612 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 1 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 304 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 14 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 94 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 5 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 4599 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 103 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 17 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 232 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 16 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 70 records from Total foraminifera counts of multinet M21/5_MSN731. 14 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 2 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1123 records from Planktic foraminifera abundance of Hole 72-516F. 1803 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1 records from Benthic foraminifera abundance of Hole 96-624. 523 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 569 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 11 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 8 records from Microzooplankton abundance and biomass at station TT050_17-4. 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 65 records from DBL_Life. 1395 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 10 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 623 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 1175 records from Océanopolis mammifères marins en Bretagne 1993-2015. 21020 records from BLS Rare and Threatened Lichen Records: England. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 1 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 116 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 1482 records from Nannofossil abundance of Hole 94-607. 1961 records from Thrips (Thysanoptera) in Norway. 69 records from Entdeckertour am Muldestausee 1/05. 97 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 1480 records from Chronicle of Nature - Phenology of Plants of State Environmental Institution National Park Braslav lakes. 2007 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 108 records from BIRDRACE Diesmal sehen wir mehr. 3 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 1134 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 1346 records from Weevils of Poland. 5 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1757 records from Arachnida of Costa Rica (INBio). 119392 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 474 records from Données du/de la naturaliste VINCENT Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 5044 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 1652 records from Algae collection. 2 records from Données du/de la naturaliste delzons olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from A new species of Phyllodytes Wagler, 1830 (Anura, Hylidae) from the Atlantic Forest of southern Bahia, Brazil. 9269 records from Relative abundance of benthic foraminifera in sediment core M5/2_KL15. 5 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 36 records from Chronicle of Nature - Phenology of Mammals of Tigirek State Nature Reserve. 60 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 4204 records from Données naturalistes de Jean-Paul LECHAPT. 3 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 2126 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 1 records from Eco-Stratégie_2017_12_18. 6 records from Guinea-Bissau Herpetological Collection - IICT. 7 records from A new species and new records of minuta - group Gnamptogenys from Brazil (Hymenoptera: Formicidae). 967 records from Inventaire des Odonates. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 907 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 1315 records from Camera trapping bird data. 31 records from Species of Ancistrus (Siluriformes, Loricariidae) from Ecuador, with the description of a new species from the Amazon River Basin. 506 records from Crustáceos macrobénticos de la plataforma y talud continental del Golfo de México. 1 records from Validation of Tethya samaaii Ribeiro & Muricy, 2011, replacement name for the sponge Tethya rubra Samaai & Gibbons, 2005 (Demospongiae, Tethyida, Tethyidae). 20 records from Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 12 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 2044 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 385 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 120 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 23 records from AlgaTerraMovies. 266 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 390 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 2 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 28 records from (Table 1) Biometrics and lipid content of polar bear (Ursus maritimus) adipose tissue between 1991-2007. 249 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 113244 records from Abondances et caractéristiques biologiques des poissons échantillonnés par pêche électrique (sauf indices d'abondance spécifiques) sur l'Oir depuis 1988 (France).. 16664 records from Hydrate Ridge, OR - Deep sea cold seep ecosystem Targeted Locus (Loci). 353 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 21 records from Benthic macrofauna abundance of sediment core 13200-047. 6279 records from SPC CoFish Fish Observations Palau 2007. 27 records from synthese_Protistdiversity_KG. 2 records from A new genus and species of Onciderini Thomson, 1860 (Coleoptera: Cerambycidae: Lamiinae) from Ecuador, with notes on additional taxa. 73490 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 51 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 76 records from Caracterización Floristica del Páramo Tatamá. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 32482 records from Amphibiens et Reptiles de France métropolitaine (Enquête 1). 555 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 26 records from Macroinvertebrados de la ciénaga La Honda, Tanguí. 285338 records from Natural England Marine Monitoring surveys. 833 records from Range table from benthic foraminifers in ODP Hole 139-857A. 148 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 186 records from Les spermaphytes de l'Herbier du Centre National de Floristique de Côte d'Ivoire: deuxième partie.. 3 records from A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group. 356 records from POPA- Fisheries Observer Program of the Azores: Sea bird sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 2 records from The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VI. Description of Ambohitantella banari gen. et sp. n. with notes on Nearticerodes Jeannel, 1954 and Triceratomerus Jeannel, 1960. 22 records from Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae). 594 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/544-6. 122 records from Foraminifera species abundances from tow TT011_10-MOC71. 1 records from New Cheilostomata (Bryozoa) species from sublittoral and bathyal zones off the Faroe Islands, with some comments on allied taxa. 2867 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 2665 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/12. 2 records from Dima spicata Schimmel, 1999 (Elateridae: Dimini), a morphologically remarkable species endemic to China. 10345 records from (Appendix A) Abundances of planktonic foraminifera in mid-Pleistocene sediments of ODP Site 184-1144 in the South China Sea. 242 records from (Table 1) Bottom fauna Metazoa in grab samples from the Namibia shelf in the area of Benguela upwelling. 14 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 3112 records from Environment Agency Eiseniella tetraedra Records (England). 103 records from Range table from planktonic foraminifers in ODP Hole 170-1040B. 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 3 records from Taxonomic studies on the genus Orancistrocerus van der Vecht, 1963 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 10 records from Microzooplankton abundance and biomass at station TT050_7-9. 832 records from Coleoptera Collection. 168 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 7 records from Inventaire et suivi Ecrevisses. 196 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 5 records from Four new species and new records of Manota (Diptera: Mycetophilidae) from Sulawesi, Indonesia. 2128 records from Occurrence (present/absence) and abundance of zooplankton in Murchison Bay, Lake Victoria. 371 records from Planktic foraminifera and paleoclimate temp
Keywords: GBIF; biodiversity; species occurrences